EVALUASI PEMERIKSAAN Treponema pallidum RAPID (TP-RAPID) dan Treponema Pallidum Haemagglutination Assay (TPHA) PADA KELOMPOK WANITA PEKERJA SEKS DI KOTA BANDUNG - Fitri Rahmi Fadhilah; Suyarta Efrida Pakpahan; Rifa Atika; Nada Reliani (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2023)
Female Sex Workers are one of the high risk group of sexually transmitted diseases like syphilis caused by Treponema pallidum. Treponema pallidum Haemagglutination Assay and Treponema pallidum Rapid (TP-Rapid) examinations are used to detect specific antibodies against Treponema pallidum, which is called the treponema test. This research aimed to determine the difference between the result of TP-Rapid and TPHA examinations in the Female Sex Workers in Bandung. This method of research is descriptive. This research starting with observations on female sex workers, the samples were examined by TP-Rapid immunochromatography method and TPHA hemagglutination method and the results of TP-Rapid examination were compared with the results of TPHA examination. The results of TP-Rapid examination obtained 7% reactive samples and 93% non-reactive sample The results of the TPHA examination obtained 33% reactive samples and 67% non-reactive samples. The reactive results on the TP-Rapid and TPHA examinations showed a difference of 26%. The conclusion of the study is that there are differences in the results of syphilis examination using the TP-Rapid and TPHA methods with p value=0,038.